Performance analysis of a time-threshold based bandwidth allocation scheme for data calls in cellular networks - Candan, Idil; Salamah, Muhammed (My University, 2006)
In this paper, we developed an analytical model of a time-threshold based bandwidth allocation scheme for data calls in cellular networks. The scheme is based on monitoring the elapsed real time of handoff calls and according to a time threshold parameter, handoff calls are either prioritized or treated as new calls. The scheme is modeled using a one-dimensional markov chain and numerical analysis is presented to estimate blocking probabilities of new calls, dropping probabilities of handoff calls and system utilization. The scheme is simulated under different network conditions. It is observed that analytical results closely match the simulation results. The results show that the proposed scheme yields a considerable enhancement in terms of performance/cost ratio when compared with the conventional schemes. © IEEE.
2nd International Conference on Systems and Networks Communications, ICSNC 2006 --
Keywords: Call admission control; Cellular networks; Handoff; Markov process